Gaming Methods in Engineering Systems Research. Issue 6 (2nd November 2017) - Grogan, Paul T.; Meijer, Sebastiaan A.
ABSTRACT: Recent interest in applications of games and gaming methods has stimulated discussion of their use in engineering systems research. Simulation games or gaming simulations are interactive environments which simultaneously model a technical system through simulation and a social system with role‐play participants. Their boundary‐spanning nature aligns with challenges in engineering systems to consider both technical and social factors in design. This paper outlines a class of gaming methods for research in engineering systems. Key contributions synthesize diverse bodies of literature to classify gaming applications as generating generalizable and contextual knowledge to benefit participants and principals, identify intellectual foundations in related social sciences, and describe the dual purpose of games as a research method for analytical or design science objectives. Conclusions highlight opportunities and challenges for gaming research methods to accommodate social science research in design‐centric activities.